Characteristics of airborne particles emitted from typical indoor combustion sources - Geng, Chen; Wu, Xinyuan; Wang, Tao; Fu, Hongbo (Frontiers in Public Health, 2025)
Combustion is an important source of indoor emissions, and exposure to combustion emissions not only concerns the quality of life of individuals but also directly affects the overall health level of society. To date, very few studies have examined the size-resolved emission characteristics of airborne particulate matter (PM) emitted from indoor sources. The study examined PM emissions from the specified combustion sources. PM concentrations and emission factors for metals and polycyclic aromatic hydrocarbons (PAHs) were analyzed under identical burning durations. Particle size distributions were determined, and dissolved organic matter (DOM) components were characterized using fluorescence spectroscopy. Health risk assessments were conducted to identify major carcinogenic risks among the emitted components. The results revealed distinct trends in PM concentrations and emission factors among the combustion sources, with cigarettes exhibiting the highest levels followed by mosquito coils and candles. The peak diameters of PM number concentration were found to be 68.5 nm for mosquito coils, 105.5 nm for cigarettes, and 201.7 nm for candles. Fine fraction (PM0.056–3.2) had significantly higher emission factors than coarse fraction (PM3.2–18), with the highest emission factor observed within the particle range of 0.18-0.32 μm. DOM from burning mosquito coils and cigarettes comprised two primary components: a protein-like (C1) and a humus-like (C2) fluorescent component. Health risk assessments indicated that chromium and benzo[a]pyrene posed the greatest carcinogenic risks among metals and PAHs in typical indoor combustion environments. Our results were primarily helpful to determine the characteristics of the PM from combustion emissions and also significant to ensure public health protection, especially for people who usually spend time indoors.